2009
DOI: 10.1364/ol.34.000887
|View full text |Cite
|
Sign up to set email alerts
|

Three-photon infrared quantum cutting from single species of rare-earth Er^3+ ions in Er_03Gd_07VO_4 crystalline

Abstract: An effective three-photon IR quantum cutting excited by visible light used for solar cells, which has attracted broad attention of academia recently, is reported for the first time (to our knowledge). It is based on a single species of rare-earth Er3+ ion of Er0.3Gd0.7VO4 crystalline. It was found that the approximate quantum cutting efficiency of the 1532.5 nm 4I13/2-->4I15/2 fluorescence, when the 2H11/2 level was excited, is about 178.55%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…34 The NIR quantum-cutting has been demonstrated in various Ln 3+ -Yb 3+ (Ln = Tb, Tm, Pr, Er, Nd, Ho, and Dy) co-doped systems (Table 3) [223][224][225][226][227][228][229][230][231][232][233][234][235][236][237] and in phosphors with a single luminescent center (Ho 3+ , Tm 3+ , or Er 3+ ). [238][239][240][241][242][243] Several mechanisms responsible for the NIR quantumcutting are illustrated in Fig. 13.…”
Section: 1 Concepts Of Quantum-cuttingmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The NIR quantum-cutting has been demonstrated in various Ln 3+ -Yb 3+ (Ln = Tb, Tm, Pr, Er, Nd, Ho, and Dy) co-doped systems (Table 3) [223][224][225][226][227][228][229][230][231][232][233][234][235][236][237] and in phosphors with a single luminescent center (Ho 3+ , Tm 3+ , or Er 3+ ). [238][239][240][241][242][243] Several mechanisms responsible for the NIR quantumcutting are illustrated in Fig. 13.…”
Section: 1 Concepts Of Quantum-cuttingmentioning
confidence: 99%
“…Representative examples have been reported for single ions like Ho 3+ , Tm 3+ , or Er 3+ . [238][239][240][241][242][243] However, one major problem presented by single ion-based quantum-cutting is the unwanted emissions in the ultravioletvisible spectral range and nonradiative recombination that compete with the desired emission of two NIR photons.…”
Section: 1 Concepts Of Quantum-cuttingmentioning
confidence: 99%
“…The quantum yields of Yb 3+ emission upon Ce 3+ 5d level excitation is lower than the expected value based on the ideal quantum cutting mechanism. 5 Recently, it was reported that the energy conveyance from high energy photons to NIR photons in Er 3+ ions involves a three-photon process, 13 which means that the theoretical quantum cutting may exceed 200%. However, Er 3+ only shows very weak and narrow absorption in 300-500 nm region.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 3. The possibility of using the 1540 nm emission of Er 3 + single doped materials in germanium cells has been recently proposed [24].…”
Section: Spectramentioning
confidence: 99%